Peru 2007-2025: An application of the Harrod, Solow and Thirlwall growth models - Erquizio Espinal, Alfredo (2007)
With the purpose of establishing a prospective of the Peruvian economy until the year 2025 based on the growth models of Harrod, Solow and Thirlwall, the author applies his parameters to Peru and calculates two scenarios of growth of GDP and GDP per person: inertial and desirable. He then reflects on the implications of the rates obtained in terms of their viability, taking into account the recent past, the results of other foresight exercises, and the pending economic reform agenda.